Metric Regularity Relative to a Cone - Van Ngai, Huynh; Tron, Nguyen Huu; Théra, Michel (Vietnam journal of mathematics, 2019)
The purpose of this paper is to discuss some of the highlights of the theory of metric regularity relative to a cone. For example, we establish a slope and some coderivative characterizations of this concept, as well as some stability results with respect to a Lipschitz perturbation.